Peningkatan Literasi Digital dan Kemandirian Belajar Siswa SMPN 11 Samarinda Melalui Pelatihan Pemanfaatan AI NotebookLM - Rahmat Riyadi; Dimas Firjatullah Islamay; Muhammad Ridwanansyah Rahman; Ega Clearesta Hananta; Ramadiani Ramadiani; Rosmasari Rosmasari (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2026)
The development of Artificial Intelligence (AI) in education is accelerating rapidly. However, the increasingly accessible use of AI without adequate digital literacy risks encouraging instant learning patterns that can weaken students' critical thinking skills. This community service activity aims to improve the digital literacy and independent learning skills of students at SMPN 11 Samarinda through the utilization of Google NotebookLM as a grounded AI. The activity was implemented using participatory and learning-by-doing methods, which were divided into three main stages namely an introduction to basic AI concepts, education on the ethical use of AI, and hands-on practice in using NotebookLM. The evaluation of students' comprehension was measured using a post-test instrument at the end of the activity to obtain an accurate picture of their actual understanding post-training. The results of this activity indicate a positive response and an increase in students' understanding of basic AI concepts, their ability to operate NotebookLM, and the growth of digital ethics awareness. Furthermore, this activity successfully produced a digital learning module that can be used as an alternative guide for continuous learning at the school.